ANALISIS HUKUM TERHADAP TINDAK PENGANIAYAAN YANG MENGAKIBATKAN KEMATIAN YANG DILAKUKAN OLEH ANAK (Studi Kasus Putusan No: 12/Pid.Sus/2022/PN.Sbr) - Sugiarto, Agus; Hermawan, Asep; Fadillah, Dila Putri; Fajar P.D (Fakultas Hukum Universitas Nahdltul Ulama Cirebon, 2022)
In this case, the facts in the trial are oriented towards a legal analysis of the Panel of Judges' decision in case No. 12/Pid.Sus/2022/PN Sbr, namely from the application of the article, the differences in witnesses presented, the elements of the crime, the aggravating and mitigating elements, the evidence presented, and the aspect of the sentencing. Considerations affect the injunction/dictum. The legal analysis is seen in the application of the article which deviates from the provisions of the principle of lex specialis derogat legi generali in this case the Public Prosecutor uses general rules in the application of the article and deviates from the Special Rules of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, in this case the judge uses the Relative Theory which emphasizes the benefits of punishment for the future of the perpetrator. The sentence is not imposed quia peccatum est (because a person commits a crime) but rather ne peccaetur (so that a person does not commit a crime). In other words, the Panel of Judges in considering this decision emphasizes the child's future, so the decision is made which is most beneficial for the child.